Degradation of ciprofloxacin in water by advanced oxidation process: kinetics study, influencing parameters and degradation pathways. Issue 5 (3rd March 2016) - Sayed, Murtaza; Ismail, M.; Khan, Sanaullah; Tabassum, Safia; Khan, Hasan M.
ABSTRACT: Gamma-radiation-induced degradation of ciprofloxacin (CIP) in aqueous solution and the factors affecting the degradation process have been investigated. The results showed that CIP (4.6 mg/L) was almost completely degraded at an absorbed dose of 870 Gy. The kinetic studies of aqueous solutions containing 4.6, 10, 15 and 17.9 mg/L indicated that the decomposition of CIP by gamma irradiation followed pseudo-first-order kinetics and the decay constant ( k ) decreased from 5.9  ×  10 −3 to 1.6  ×  10 −3  Gy −1 with an increase in CIP initial concentration from 4.6 to 17.9 mg/L. The effect of saturation of CIP solution with N2, N2 O or air on radiation-induced degradation of CIP was also investigated. The effects of radical scavengers, such as t -BuOH and i -PrOH, showed the role of reactive radicals towards degradation of CIP in the order of . The apparent second-order rate constant of with CIP was calculated to be 2.64 × 10 9  M −1  s −1 . The effects of solution pH as well as natural water contaminants, such as, , and, on CIP degradation by gamma-irradiation were also investigated. Major degradation products, including organic acids, were identified using UPLC-MS/MS and IC, and degradation pathways have been proposed.